The Relationship Level Of Knowledge Of Mothers About Giving Mp-Asi With The Incidence Of Diarrhea In Children Aged 6-24 Months At Puskesmas Karang Pule, Mataram City - Izar Khairani; Sukandriani Utami; Baiq Novaria Rusmaningrum; Diani Sri Hidayati (Jurnal EduHealth, 2023)
Diarrheal disease is still a global problem with a high degree of morbidity and mortality in various countries and mortality in children under the age of 5 in the world. Causes include infection, malabsorption, allergies, poisoning, and inappropriate complementary feeding. The provision of MP-ASI is influenced by the type of food and the form of food according to the age of the child. Mother's knowledge plays an important role in providing complementary complementary foods (MP-ASI) so that children's nutrition is fulfilled. Objectives: This study aims to analyze the relationship between mother's knowledge about giving MP-ASI to children aged 6-24 months with the incidence of diarrhea at the Karang Pule Health Center, Mataram City. Methods: Observational analytic quantitative research with a cross sectional study design. The sample in this research is 70 respondents. The data obtained were analyzed with the Chi-Square correlation test. Results: There were 40 mothers (57.1%) who did not have a good level of knowledge about giving MP-ASI to children aged 6-24 months. There were 43 cases of diarrhea in children aged 6-24 months (61.4%). There is a significant relationship between mother's knowledge about complementary feeding and the incidence of diarrhea in children aged 6-24 months with a p-value <0.001. Conclusion: There is a relationship between mother's knowledge about giving MP-ASI and the incidence of diarrhea in children aged 6-24 months at the Karang Pule Health Center, Mataram City. 1%) who did not have a good level of knowledge about giving MP-ASI to children aged 6-24 months. There were 43 cases of diarrhea in children aged 6-24 months (61.4%). There is a significant relationship between mother's knowledge about complementary feeding and the incidence of diarrhea in children aged 6-24 months with a p-value <0.001. Conclusion: There is a relationship between mother's knowledge about giving MP-ASI and the incidence of diarrhea in children aged 6-24 months at the Karang Pule Health Center, Mataram City. 1%) who did not have a good level of knowledge about giving MP-ASI to children aged 6-24 months. There were 43 cases of diarrhea in children aged 6-24 months (61.4%). There is a significant relationship between mother's knowledge about complementary feeding and the incidence of diarrhea in children aged 6-24 months with a p-value <0.001. Conclusion: There is a relationship between mother's knowledge about giving MP-ASI and the incidence of diarrhea in children aged 6-24 months at the Karang Pule Health Center, Mataram City.